Nonlinear association between weekend sleep recovery (WSR) and insulin resistance: benefits in males and short weekday sleepers - Haidong Wang; Xiaohui Wei; Yudong Ba; Haiyan Liu; Yanhui Zhou; Weibo Wang; Lisheng Zheng (Endocrine Connections, 2025)
Background: Weekend sleep recovery (WSR), often referred to as ‘weekend catch-up sleep’ (WCS) in the prior literature, may represent a behavioral response to accumulated weekday sleep loss. However, its metabolic implications remain poorly understood. This study aimed to investigate the association between WSR duration and insulin resistance, measured by HOMA-IR, with particular focus on sex differences and weekday sleep duration stratification. Methods: We analyzed 4,036 adults (mean age: 49.62 years; 51.54% female) from NHANES 2017–2020. HOMA-IR was calculated as an indicator of insulin resistance. WSR duration was categorized as ≤0 h, 0–2 h, or >2 h. We used multivariable linear regression, stratified subgroup analyses (by sex, weekday sleep duration ≤7 vs >7 h, and different age groups), threshold effect modeling, and interaction analysis to assess associations. Results: Participants with WSR >0 h had significantly lower HOMA-IR levels compared to those with WSR ≤0 h (β = −1.16, 95% CI: −1.74 to −0.58, P = 0.0001), with the greatest benefit observed in the 0–2 h group (β = −1.14, 95% CI: −1.74 to −0.53, P = 0.0002). A nonlinear threshold effect was identified at 2 h of WSR, beyond which metabolic benefits plateaued. Stratified analyses revealed stronger effects in males (β = −0.68, 95% CI: −1.21 to −0.08, P = 0.0132) and in participants with weekday sleep ≤7 h (β = −0.39, 95% CI: −0.72 to −0.07, P = 0.0182). No significant associations were observed in females or in those with >7 h of weekday sleep. Conclusion: Moderate WSR (0–2 h) is associated with lower insulin resistance, particularly among males and individuals with weekday sleep restriction. These findings suggest that modest WSR may offer metabolic benefits in specific populations, though the effect appears to plateau beyond 2 h.